Obstructive sleep apnea: the new cardiovascular disease. Part I: obstructive sleep apnea and the pathogenesis of vascular disease - Khayat, Rami (2008)
Obstructive sleep apnea (OSA) is increasingly recognized as a novel cardiovascular risk factor. OSA is implicated in the pathogenesis of hypertension, left ventricular dysfunction, coronary artery disease and stroke. OSA exerts its negative cardiovascular consequences through its unique pattern of intermittent hypoxia. Endothelial dysfunction, oxidative stress, and inflammation are all consequences of OSA directly linked to intermittent hypoxia and critical pathways in the pathogenesis of cardiovascular disease in patients with OSA. This review will discuss the known mechanisms of vascular dysfunction in patients with OSA and their implications for cardiovascular disease.